Unconditional access to non-invasive prenatal testing (NIPT) for adult-onset conditions: a defence - Marks, IR; Mills, C; Devolder, K (BMJ, 2023)
Over the past decade, non-invasive prenatal testing (NIPT) has been adopted into routine obstetric care to screen for fetal sex, trisomies 21, 18 and 13, sex chromosome aneuploidies and fetal sex determination. It is predicted that the scope of NIPT will be expanded in the future, including screening for adult-onset conditions (AOCs). Some ethicists have proposed that utilising NIPT to detect severe autosomal AOCs that cannot be prevented or treated like Huntington’s disease, should only be offered to prospective parents who intend to terminate a pregnancy in the case of a positive result. We refer to this as the ‘Conditional Access Model’ (CAM) for NIPT. We argue against CAM for NIPT to screen for Huntington’s disease, or any other AOC. Next, we present results from a study we conducted in Australia that explored NIPT users’ attitudes regarding CAM in the context of NIPT for AOCs. We found that, despite overall support for NIPT for AOCs, most participants were not in favour of CAM for both preventable and non-preventable AOCs. Our findings are discussed in relation to our initial theoretical ethical theory and with other comparable empirical studies. We conclude that an ‘Unconditional Access Model’, which provides unrestricted access to NIPT for AOCs, is a morally preferable alternative that avoids both CAM’s fundamental practical limitations and the limitations it places on parents’ reproductive autonomy.